Introducing an Approach to Draw a Groundwater Levels Map in a n Aquifer, Including Qanats - Hojat Mirani Moghadam; Gholam Hossein Karami; Reza Barati (Water Harvesting Research)
In this research, a method of drawing groundwater levels maps is developed considering the active Qanats in the Gonabad Plain, Iran. The common approach for drawing the groundwater levels map, is interpolating the groundwater level elevation data obtained from observation wells. Qanat has been ignored for drawing the groundwater levels map in the most of time. However, it is one of the main structures that should be considered in this analysis. In the introduced approach, the groundwater surface levels map of the Gonabad Plain was drawn using the groundwater level elevation data obtained from observation wells and mother well of Qanats located in the aquifer and also considering that water bearing zone of Qanats drain groundwater, therefore groundwater levels is parallel and groundwater flow line is perpendicular to it. Results lead to preparation of an accurate groundwater levels map that is important for the maintenance of groundwater resources and also helping to reveal the secret of the method of drilling deep Qanats in the plain in several thousand years ago. By using this map, the aquifer transmissivity in water bearing zone of each Qanat and the capture zone of each Qanat were estimated. The results indicated that the aquifer transmissivity in water bearing zone of Qanats varies from 23 to 77 square meters per day.